Un nuovo genere di Eunicidae (Annelida: Polychaeta) del Golfo di Catania - Cantone, Grazia (Animalia, Catania, 1983)
The Author describes a new genus and a new species of Eunicidae Lysibranchia paucibranchiata, with 3 antennae, 5-7 pair of pectinate gills, conica! prostomium, no tentacular cirri; she gives a key to genera of the family Eunicidae.
World Polychaeta Database (WPolyDb), journal not available digitised as at September 2018